PENGEMBANGAN SISTEM PENDETEKSI BANJIR MENGGUNAKAN FUZZY DENGAN RASPBERRY PI (STUDI KASUS: KABUPATEN SAMPANG) - Dwi Puspitasari; Muhammad Thaifururrahman; Rudy Ariyanto (Jurnal Teknologi Informasi dan Terapan, 2019)
Flooding is a natural disaster that is troubling for the community. Floods occur due to overflowing water from rivers, lakes, or gutters. The flood also caused material losses and even caused casualties. Sampang Regency is one of the districts located on Madura Island which is often flooded.The Raspberry Pi is a mini computer that is capable of performing the same tasks as a computer. The use of the Raspberry Pi as a server is more efficient than using a PC server which in terms of price is very expensive. The Raspberry Pi can also be combined with various sensors because it has 40 pins as a connector. The Parallax Ping sensor is an ultrasonic sensor that can detect the distance of an object by emitting ultrasonic waves with a frequency of 40 KHz and then detecting the reflection. By using an ultrasonic sensor as a water level counter, the height value of the river will be obtained. From this height value, it is then processed using the fuzzy mamdani method to produce a river water level status. This elevation status will then be informed to the public.Based on the test results, this flood detection system uses an ultrasonic sensor as a water level meter that is controlled by the Raspberry Pi. Data from ultrasonic sensors then calculated by fuzzy mamdani method can produce water level status. The water level status is obtained from the height data of the water surface calculated by using an ultrasonic sensor. The water level status is then sent to a cellphone number using a wavecom modem.